Bioactive constituent characterization and antioxidant activity of ganoderma lucidum extract fractionated by supercritical carbon dioxide - Mei, Su Lin; Zer, Ran Yu; Be, Jen Wang; Cheng, Chi Wang; Yih, Ming Weng; Malcolm Koo (Universiti Kebangsaan Malaysia, 2015)
Ganoderma lucidum has been recognized as a precious fungus in both Chinese and Japanese traditional medicine for centuries. It contains many bioactive ingredients such as triterpenoids and polysaccharides. The present study used supercritical carbon dioxide (SC-CO2) fractionation to fractionate Ganoderma lucidum extract into four fractions (R, F1, F2, & F3) and evaluate the correlation between the content of functional components and their antioxidant ability. Relatively high concentrations of the three types of bioactive constituents were simultaneously partitioned into different fractionation collecting vessels. The free radical scavenging ability was greatest in F1. The IC50 of DPPH scavenging ability was 0.90 mg/mL and that of ABTS radicals scavenging activity was 0.45 mg/mL. The correlation analysis of antioxidant ability with total triterpenoids and total polyphenols showed a positive relationship. In conclusion, this study showed that fractionation of Ganoderma lucidum extract using SC-CO2 fractionation technology was able to effectively partition its bioactive components including triterpenoids, polysaccharides and phenolic compounds and also to increase the antioxidant activities of the fractions.